Social Media Interactions and Stock Price Bubble: A Case Study of GameStop - Ngo Minh , Vu; Nguyen Huu , Huan (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
Financial market bubbles have recently created serious problems for sustainable economic growth for all countries worldwide. Therefore, this study aims to explore the relationship between social interaction and stock market bubbles and explain the causes and development of financial market bubbles. Using a set of over 286,000 Twitter posts related to GameStop stock prices from December 2020 to the end of February 2021 and network analysis methods through Gephi software as well as case study methods, this study investigates the interaction between investors on social media and the impact of these social network connections on the formation and development of the GameStop stock price bubble in early 2021. The results show that there are 5 networks formed between investors and significant differences in the level of connectivity between users as well as different levels of information dissemination in each network that significantly affect the volatility of the GameStop stock price. This study may support investors, securities companies, and government agencies in understanding the social behavior of investors, as well as monitoring and preventing price bubbles.
Keywords: Social media; Twitter; Assets bubble; GameStop; Investors’ behaviors